2022
DOI: 10.1155/2022/7686728
|View full text |Cite|
|
Sign up to set email alerts
|

BAP31 Promotes Proliferation, Invasion, and Metastasis of Liver Cancer Cells via Activating PI3K/AKT Pathway

Abstract: Background. Many breakthroughs have been made in the clinical treatment of liver cancer, but there are still many liver cancer patients with limited treatment methods. Therefore, it is very important to find targets for early diagnosis and specific treatment of liver cancer. Methods. During the operation, 32 pairs of tumor tissues and corresponding normal liver tissues were acquired from patients. The mRNA expression was measured by qPCR. The protein expression was evaluated via Western blot. Flow cytometry as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 21 publications
3
7
0
Order By: Relevance
“…In the present study, the DEGs in the livers between treated with and without MnCl 2 on the 1st, 3rd, and 5th day were involved in PI3K/Akt signaling pathway (Fig. 3A-C), which was consistent with previous studies [35][36][37][38]. For example, Sun et al (2022) reported that PI3K/Akt signaling pathway mediated liver steatosis and increased cell survival [35].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In the present study, the DEGs in the livers between treated with and without MnCl 2 on the 1st, 3rd, and 5th day were involved in PI3K/Akt signaling pathway (Fig. 3A-C), which was consistent with previous studies [35][36][37][38]. For example, Sun et al (2022) reported that PI3K/Akt signaling pathway mediated liver steatosis and increased cell survival [35].…”
Section: Discussionsupporting
confidence: 91%
“…3A-C), which was consistent with previous studies [35][36][37][38]. For example, Sun et al (2022) reported that PI3K/Akt signaling pathway mediated liver steatosis and increased cell survival [35]. In addition, PI3K/Akt signaling pathway activation not only induced lipid metabolism disorder and insulin resistance [36], but also increased the hepatic glycogen content and was associated with glucose homeostasis [37].…”
Section: Discussionsupporting
confidence: 87%
“…BAP31 primarily resides in the endoplasmic reticulum, which functions as a chaperone for specific transmembrane proteins and as a regulator of apoptosis [17]. It has been reported that BAP31 can regulate the expression of specific anti-apoptotic or apoptotic factors, including Bcl-2 and Bax, in certain cell types [18,32]. In this study, we found that knockdown of BAP31 enhanced apoptosis and increased Dox-induced apoptosis in HCC cells.…”
Section: Discussionsupporting
confidence: 48%
“…BAP31 is emerging as an attractive therapeutic target for cancer. For example, Sun et al reported that BAP31 promotes proliferation, invasion, and metastasis of liver cancer cells [18]. Dang et al reported that BAP31 regulates proliferation, migration, and invasion to promote cervical cancer progression [17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation